Eliminating weapons of mass destruction : prospects for effective international verification - Andemicael, Berhanykun (Global issues series (Palgrave Macmillan (Firm)), 2005)
Recent events have shown that, despite over 40 years of effort, control of weapons of mass destruction (WMD) and effective deterrence against their use are still inadequate. Cooperative solutions through verified disarmament are the best responses to this problem. The book examines the three verification organizations that form the core of the emerging WMD control regime - the International Atomic Energy Agency (IAEA) and the organizations established under the Comprehensive Test-Ban Treaty (CTBT) and the Chemical Weapons Convention (CWC) A comparative study shows how their role can be strengthened and used as a foundation for a more complete regime, beginning with the creation of a verification mechanism for the Biological Weapons Convention (BWC). The United States is presently sceptical about the value of international verification. The book addresses the verifiability issue by analysing the strengths and weaknesses in each organization and recommending ways to strengthen the process and enhance its management. It then focuses on the crucial issues of compliance and recourse and explores the broader political and security issues bearing upon any efforts to repair and further develop the WMD control regime.